The Relationship Between Macroeconomic Factors and Profitability of Reinsurance Companies in Africa: An Application of System GMM-Model - NZUZA, Zwelihle Wiseman; MSOMI, Thabiso Sthembiso (PT Keberlanjutan Strategis Indonesia, 2023)
Despite the known strengths of the reinsurance companies to generate immense profits, evidence from existing literature indicates that the future of the reinsurance companies needs to be more robust to economic deficiencies leading to underperformance. There are many possible factors behind this. However, this study aimed to determine the relationship between macroeconomic factors and the profitability of African reinsurance companies with a Generalized Method of Moments (GMM) model. The study used 121 listed reinsurance companies from 48 African countries using secondary data from year 2008 to 2019. A 1452 observation panel data set was analyzed using conventional least squares and two-step System GMM estimators. The study revealed that GDP, interest rate, and the exchange rate positively impact profitability. In contrast, the inflation rate and money supply revealed a negative and negligible impact on profitability. The input of this research resides in providing new evidence on the macroeconomic factors influencing the profitability of listed reinsurance companies in Africa.